Analysis of determinant factors affecting treatment compliance of hypertensive patients - Iva Fauziani; Anwar Ramli; Julia Fitrianingsih (Jurnal Ilmiah Kesehatan Sandi Husada, 2024)
Introduction: Hypertension requires regular and controlled treatment to stabilize blood pressure and prevent complications. Many hypertensive patients do not comply with hypertension treatment procedures, including medication. Objective: This study aimed to analyze the determinant factors influencing medication compliance in hypertensive patients. Methods: The research method used was observational analytic with a cross-sectional design. Data collection using a questionnaire. The sample in this study was 67 hypertension patients. Data analysis used the chi-square test. Result: The results of this study indicate that there is an influence of the level of knowledge (p = 0.045), motivation to seek treatment (p = 0.000), and family support (p = 0.000) on medication compliance in hypertensive patients. Conclusion: Motivation to seek treatment is the most dominant variable on compliance with the treatment of hypertension patients. Health workers must develop an educational strategy focusing on increasing patient motivation.